Smart Superhyrophobic Coating for Corrosion Protection - Nurathilah Izzreen Zahreen; Norhasnidawani Johari (Journal of Advanced Research Design, 2024)
The smart superhydrophobic coating was developed via nanocomposite approach using nanocomposite which is zinc oxide (ZnO2) / epoxy with the simplest and inexpensive method involving simple equipment that convey superhydrophobicity properties which is hierarchical rough structures. However, most of the studies related to the fabrication of superhydrophobic coating are both including complex fabrication steps and multitudinous treatment steps including pre/post-treatment to develop superhydrophobicity. The physicochemical properties of the coating were studied in terms of wetting, morphological and structural bonding properties via FESEM, EDS and FTIR. The smart superhydrophobic coating exhibited excellent water adhesion, water repellence and self-cleaning property with WCA = 166.60° and SLA = 5° respectively. The corrosion performance of coating was investigated through salt spray condition, through visual inspection and study of wetting properties for 20 days of exposure times with ASTM B117 standard testing, 3.5 % NaCl solution. The WCA was observed and recorded to make sure the coating maintaining its superhydrophobicity even after being exposed harsh environment. The resulted coating function effectively as corrosion protection and perform a self-cleaning coating which also helps in reducing maintenance and corrosion-related costs.